Metagenomic analysis of bacterial and archaeal assemblages in the soil-mousse surrounding a geothermal spring - Bhatia, Sonu (Genom Data, 2015)
The soil-mousse surrounding a geothermal spring was analyzed for bacterial and archaeal diversity using 16S rRNA gene amplicon metagenomic sequencing which revealed the presence of 18 bacterial phyla distributed across 109 families and 219 genera. Firmicutes, Actinobacteria, and the Deinococcus-Thermus group were the predominant bacterial assemblages with Crenarchaeota and Thaumarchaeota as the main archaeal assemblages in this largely understudied geothermal habitat. Several metagenome sequences remained taxonomically unassigned suggesting the presence of a repertoire of hitherto undescribed microbes in this geothermal soil-mousse econiche.